(untitled) (Journal of the College of Basic Education, 2019)
The researcher used the experimental method to design one group with pre and post tests for a sample of (10) players from Hit Sports Club in the ball. Before the exercises were applied, and included (36) training units distributed over (12) weeks and an average of (3) units per week. Researcher appropriate statistical methods in order to reach results and the most important conclusion of the exercises Albulaomitrih positive impact in the development of motor response speed and also concluded the existence of a function correlation statistically between the motor response speed and the skills of the transmission wall block, any development of the reception in the motor response speed leads to performance skills development